Critical and Creative Thinking and Theory Application in Social Sciences Research Studies: A Sociological Musing - Major Elazia, Paul; Amateshe, Maurice; Shinachi Wanyonyi, Michael; Wisindi, Andrew; Leonard Chilimo, Wanyenda; Nangila Makokha, Arnety; Ngugi, Margaret (Multidisciplinary Journal of Technical University of Mombasa, 2024)
Critical and creative thinking are important in the application of theories in social research. However, sociology theories remain extant in many studies mainly because of the failure of researchers to apply critical and creative thinking in social research studies. This is attributed to inadequate skills for the pragmatic application of philosophical techniques of using theories to guide research work. This paper seeks to elucidate this problem within scholarly undertakings for post-graduate students and other scholars who must use critical and creative thinking in inculcating theories into their studies. The paper intends to elicit an in-depth discussion amongst social scientists on the best way to address these challenges. This paper moves further and proposes how sociological theories are integrated into social research studies and guide the construction and process of research from conceptualization, proposal writing, data collection, analysis, and report writing by focusing on specific theories a study may adopt.
Keywords: Critical and creative thinking; Philosophical techniques; Social research; Sociological theories